2011
DOI: 10.1007/s12199-011-0256-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cigarette smoking on paraoxonase 1 activity according to PON1 L55M and PON1 Q192R gene polymorphisms

Abstract: Objective This study aims to investigate the effect of cigarette smoking on paraoxonase 1 (PON1) activity according to PON1 L55M and PON1 Q192R gene polymorphisms. Materials and methods Our sample included 300 voluntary subjects: 138 nonsmokers and 162 current smokers aged 38.47 ± 21.91 and 35.55 ± 16.03 years, respectively. PON1 activity was determined by kinetic methods. L55M and Q192R gene polymorphisms of PON1 were determined by multiplex polymerase chain reaction (PCR) restriction fragment length polymorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 22 publications
3
22
1
1
Order By: Relevance
“…As described in the literature about different populations [5,28,[35][36][37], we noted that PON1 activity reached its maximum for LL and RR genotypes and its minimum for MM and QQ genotypes in patients and in controls. We therefore concluded that LL and RR genotypes may be protective against oxidative damage of lipoprotein by decreasing peroxidation of LDL by HDL.…”
Section: Discussionsupporting
confidence: 77%
“…As described in the literature about different populations [5,28,[35][36][37], we noted that PON1 activity reached its maximum for LL and RR genotypes and its minimum for MM and QQ genotypes in patients and in controls. We therefore concluded that LL and RR genotypes may be protective against oxidative damage of lipoprotein by decreasing peroxidation of LDL by HDL.…”
Section: Discussionsupporting
confidence: 77%
“…42 A recent study showed that cigarette smoking is significantly associated with a decrease in PON1 activity. 38 Besides, higher plasma oxidized LDL levels have been found in smokers, 43 and also, the mean plasma oxidized LDL levels in patients with AMD was found to be significantly higher than in the controls. 22 Otherwise, nicotine has been found to stimulate neovascularization by inducing endothelial cell proliferation and accelerating fibrovascular growth 44 and also to increase severity of choroidal neovascularization.…”
Section: Discussionmentioning
confidence: 94%
“…It has also been shown in a recent study that cigarette smoking is significantly associated with a decrease in PON1 activity. 38 There have also been associations found between atherosclerosis, systemic hypertension, obesity, and AMD. [39][40][41] In our study, the frequency of smoking was higher in AMD patients than in controls and was found to be associated with an increased risk of AMD (odds ratio = 2.34; P = 0.003) after adjusting for confounding variables (age, gender, hypertension, diabetes, and hypercholesterolemia).…”
Section: Discussionmentioning
confidence: 99%
“…Полиморфизм L55M A>T (rs854560) гена PON1 определяет содержание параоксоназы 1 в крови, а именно, наличие аллеля 55L в генотипе связано с более низким содержанием фермента по сравнению с вариантом 55М [10]. Однако более высокое содержание параоксоназы 1 у лиц-носителей аллеля 55М приводит к понижению стабильности параоксоназы 1, что может резко снижать ее активность, особенно под действием внешних факторов, например, таких, как курение [15]. Психовегетативные нарушения, ассоциированные с присутствием в генотипе 55М аллеля полиморфизма L55M A>T гена PON1, у обследованных лиц, вероятно, могут быть обусловлены меньшей стабильностью фермента параоксоназы в сыворотке крови, и, следовательно, снижением антиокислительных и антиатерогенных свойств данного фермента, что, в свою очередь, приводит к изменению функционирования нервной системы и развитию ее дисфункции.…”
Section: таблицаunclassified